2021
DOI: 10.1111/1365-2745.13606
|View full text |Cite
|
Sign up to set email alerts
|

Combining conservation status and species distribution models for planning assisted colonisation under climate change

Abstract: Effects of climate change are particularly important in the Mediterranean Biodiversity hotspot where rising temperatures and drought are negatively affecting several plant taxa, including endemic species. Assisted colonisation (AC) represents a useful tool for reducing the effect of climate change on endemic plant species threatened by climate change. We combined species distribution models (SDMs) for 188 taxa endemic to Italy with the IUCN red listing range loss threshold under criterion A (30%) to define: (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 100 publications
(106 reference statements)
1
15
0
Order By: Relevance
“…Although urban sprawl is among the main drivers of habitat loss and degradation, cities also offer suitable habitat islands (Angold et al, 2006;Niesner et al, 2021) and can function as stepping stones (Saura et al, 2014;Lynch, 2019), if functional connectivity -exchange of genes, biomass or energy -is prevailing (Baker and Harris, 2007;Braaker et al, 2014). However, urban wildlife faces increasing challenges due to growing anthropogenic pressure and predicting the distribution of species in anthropogenic areas is therefore a crucial factor for urban wildlife conservation and should build the basis for urban planning (Fajardo et al, 2014;Casazza et al, 2021). Species distribution models (SDMs) quantify the relationship between observations of a species and the underlying environmental gradients (Araújo and Guisan, 2006;Guisan et al, 2017), and they encompass occupancy frameworks, machine-learning algorithms and hierarchical modeling frameworks (Elith and Leathwick, 2009;Kéry et al, 2010;Dorazio, 2014;Hefley and Hooten, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although urban sprawl is among the main drivers of habitat loss and degradation, cities also offer suitable habitat islands (Angold et al, 2006;Niesner et al, 2021) and can function as stepping stones (Saura et al, 2014;Lynch, 2019), if functional connectivity -exchange of genes, biomass or energy -is prevailing (Baker and Harris, 2007;Braaker et al, 2014). However, urban wildlife faces increasing challenges due to growing anthropogenic pressure and predicting the distribution of species in anthropogenic areas is therefore a crucial factor for urban wildlife conservation and should build the basis for urban planning (Fajardo et al, 2014;Casazza et al, 2021). Species distribution models (SDMs) quantify the relationship between observations of a species and the underlying environmental gradients (Araújo and Guisan, 2006;Guisan et al, 2017), and they encompass occupancy frameworks, machine-learning algorithms and hierarchical modeling frameworks (Elith and Leathwick, 2009;Kéry et al, 2010;Dorazio, 2014;Hefley and Hooten, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Araucaria forest) (Donoso 2006, Luebert andPliscoff 2006), here we showed that each species can also harbor its particular set of environmental constrains. This species-specific set of constrains might be relevant to guide climate change mitigation projects through assisted migration programs for focal species in this hotspot (Casazza et al 2021). This strategy can be especially relevant for endemic species that might not be able to follow rapid changes in climate, as they may have little dispersal capacity (Essl et al, 2011), and/or a reduced climatic niche, so negative effects of warming and climate change deepen their survival (Ozinga et al 2009), particularly for cold tolerant species.…”
Section: Enm For Focal Speciesmentioning
confidence: 99%
“…The term translocation has typically been used in the context of reintroduction whereby a population of a threatened species is Whereas Casazza et al (2021) found that translocation of narrow endemics might involve just a handful of sites to offset climate losses, we expect that dominant tree species threatened within their range (e.g. coast redwood) would have to be translocated at a landscape level to protect overall habitat, ecosystem productivity and associated species.…”
Section: Pl Ant Tr An S Lo C Ati On S a S Soluti On S To Climate-indu...mentioning
confidence: 99%
“…For each species, they calculated the number of translocation attempts needed to compensate for declines in climatically suitable habitat within the historical limits of a species geographical range. Under optimistic climate change scenarios, range losses for all species were below the threshold of 30% reduction—the range loss required to change a Red List categorisation from Least Concern to Vulnerable (Casazza et al., 2021). This suggested that none of the 188 species required translocation to avoid a recognised deterioration in conservation status by 2080.…”
Section: Plant Translocations As Solutions To Climate‐induced Biodive...mentioning
confidence: 99%
See 1 more Smart Citation